Employee Performance of National Population and Family Planning Board North Sumatera, Based on: Internal Work Environment, Training and Corrective Discipline - Batubara, Suci Hairunisa; Syamsuri, Abd. Rasyid; Fikri, Muhammad Hilman; Hutasuhut, Julianto (Garuda Prestasi Nusantara Consulting, 2022)
The purpose of this study is to examine how the internal work environment, training, and corrective discipline affect the performance of the staff at the North Sumatra National Population and Family Planning Board. Quantitative research is the method employed. In this survey, 89 employees made up the population. employing saturated samples drawn from the entire population for sampling. Observation, documentation studies, and questionnaires were the data collection methods employed. Multiple linear regression using the statistical product software solution (SPSS) program is the analytical approach used in this study. The study's findings demonstrate that the National Population and Family Planning Board of North Sumatra's employees perform better as a result of their internal working environment in a favorable and significant way. The performance of the staff of the National Population and Family Planning Board of North Sumatra is positively and significantly impacted by training. The effectiveness of the North Sumatra National Population and Family Planning Board's personnel is significantly and favorably impacted by corrective discipline. The National Population and Family Planning Board of North Sumatra's staff perform better as a result of their internal working environment, training, and corrective discipline. The internal work environment, training, and corrective discipline may all account for 63.3% of employee performance according to this study's coefficient of determination (R2), which is 0.633.